The Relationship Between the Burnout Syndrome Dimensions and Body Mass Index as a Moderator Variable on Obese Managers in the Mexican Maquiladora Industry - Armenta-Hernández, Oziely; Maldonado-Macías, Aidé; Camacho-Alamilla, María del Rocío; Serrano-Rosa, Miguel Ángel; Baez-Lopez, Yolanda Angélica; Balderrama-Armendariz, Cesar Omar (Frontiers in Psychology, 2021)
Abstract: Burnout syndrome (BS) and obesity are two growing conditions that affect employees’ health and company productivity. Recently, several studies have pointed to a possible relationship between both phenomena. However, such a relationship has not been clearly defined. This research analyzes the relationship between BS dimensions and body mass index (BMI), the latter being treated as a moderator variable among obese senior and middle managers in the Mexican maquiladora industry through a structural equation model. A total of 361 senior and middle managers (124 of them classified as obese under the World Health Organization’s (WHO) criteria) completed both the Maslach Burnout Inventory-General Survey (with emotional exhaustion, cynicism, and professional efficacy as subscale dimensions) and a sociodemographic questionnaire (which included BMI). The results showed a statistically significant relationship between emotional exhaustion and professional efficacy (P<0.001; β = -0.320), with BMI acting as a moderator variable. The results showed that when BMI increases as a moderator variable, the strength of the relationship between emotional exhaustion and professional efficacy also changes. For example, although professional efficacy had a negative value of 0.14 before the moderator effect, the value increased up to 0.32 when the BMI was factored into the relationship. Therefore, maquiladora industries are being advised to increase their investments on the identification and prevention of employees’ emotional exhaustion and obesity. Such interventions would promote a better quality of life and could prevent economic losses resulting from poor employee performance.